Responses of root physiological characteristics and resistance gene expression to infection by Meloidogyne incognita at different temperatures in tobacco - Yang, Zhixiao; Chen, Qilong; Wang, Rengang; Lin, Yingchao; Kong, Dejun; Wang, Zhihong; He, Xinxi; Han, Zhujun; Guo, Yushuang; Xia, Haiqian; Cao, Yi (Frontiers in Plant Science, 2025)
Meloidogyne incognita (M. incognita) is a highly destructive species of Meloidogyne spp., characterized by its ability to cause root-knot nematode (RKN) disease, which is difficult to control and severely inhibits plant growth. Temperature is one of the primary factors affecting M. incognita infection. However, the precise underlying mechanisms have not yet been clarified. The present study aims is to further explore the temperature-influenced resistance mechanisms to M. incognita. Antioxidant enzyme activities, osmotic regulation substance contents, tissue structure changes, and expression of the resistance gene (Rk) in the roots of two tobacco varieties were analyzed under three temperatures (15°C, 25°C, and 35°C) via artificial inoculation. A M. incognita-resistant variety (NC95) and a susceptible variety (CBH) was selected as experimental materials. The results showed that the activities of peroxidase (POD) and catalase (CAT), as well as the contents of soluble sugar, proline, and hydroxyproline-rich glycoprotein (HRGP), increased to varying degrees under M. incognita infection, while superoxide dismutase (SOD) activity decreased. Notably, the activities of POD and CAT, along with the contents of soluble sugar, proline, and HRGP, were all higher in NC95 than in CBH. Meanwhile, antioxidant enzyme activities and osmotic substance contents in both varieties varied most at 25°C and least at 35°C. No giant cells or oocysts were observed in the root tissues of NC95 at any temperature, whereas numerous giant cells and oocysts were present in CBH. The number of giant cells in CBH was highest at 25°C compared to 15°C and 35°C, and the degree of lignification in NC95 was also greater at 25°C. In addition, M. incognita infection induced the expression of Rk gene in NC95, with expression levels at 25°C and 15°C higher than at 35°C. The results indicated that SOD activity and osmotic regulatory substance contents decreased in the roots of the susceptible variety under M. incognita infection, accompanied by the appearance of numerous giant cells in the xylem, contributing to susceptibility. Conversely, the resistant tobacco variety exhibited stronger capabilities in reactive oxygen species (ROS) scavenging and osmotic regulation, no significant changes in root tissue structure, and upregulated expression of the Rk gene, all of which contributed to infection inhibition. Compared with the observations at 25°C, M. incognita infectivity on tobacco roots was effectively reduced by 35°C due to increased antioxidant enzyme activities, enhanced osmotic regulatory substance contents, and well-maintained root tissue structure. Additionally, Rk gene expression was not inactivated but only reduced at 35 °C, and it remained effective in inhibiting M. incognita infection.